Ovsynch Synchronisation Programme Combined with Vitamins and Minerals in Underfed Cows: Biochemical, Hormonal and Reproductive Traits - Ucar, Omer; Ozkanlar, Seckin; Kaya, Mehmet; Ozkanlar, Yunusemre; Senocak, Mumin Gokhan; Polat, Harun (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
The aim of present study was to investigate the effects of Ovsynch synchronisation programme combined with vitamins and minerals upon biochemical, hormonal and reproductive parameters for improving post partum (pp) reproductive performance of underfed dairy cows. Thirty-six healthy cows, aged 3-10 years-old, were used with a minimum 43 days pp. Following the first blood sampling (as baseline), 25 days before synchronisation (GnRH injection), the body condition scores (BCSs, 1-5 scale) were determined. After balancing the BCSs (2.56, mean), animals were then divided into four trial groups, as control (Group I, n=7), vitamin ADE (II, n=10), mineral mix (III, n=9) and combination group (IV, n=10). Overall, the results suggest that; i) Ovsynch synchronisation programme, supplemented with vitamins and minerals, favourably affected the plasma levels of vitamin A only, ii) desirable effects of supplements upon the presence of luteal structure and ultimate pregnancy rate were evident in vitamin group only, iii) glucose (tendency) as well as some protein and lipid levels were progressively changed by negative energy balance (NEB), and iv) the low initial cyclic activity and poor BCS seemed to diminish the overall success rate of synchronisation programme used in underfed dairy cows early pp.
Keywords: Cow; Synchronisation; Vitamin; Mineral; Metabolism; Reproduction; NEB